2021
DOI: 10.3390/cancers13236094
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of the Safety of Anti-COVID-19 Nutraceuticals for Patients with Cancer

Abstract: Interest in dietary supplements and their efficacy in treating and preventing disease has increased greatly since the outbreak of the COVID-19 pandemic. Due to the risk of severe COVID-19 in patients with cancer, we conducted a narrative review aiming to better understand the data on the safety of the most efficacious “anti-COVID-19” nutraceuticals for patients with cancer. We conducted a PubMed database search aimed at identifying the most effective nutrients for use against COVID-19. For the identified nutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…A growing body of evidence based on meta-analyses, observational prospective and retrospective studies, and interventional studies has shown associations between hypovitaminosis D and the occurrence of acute severe COVID-19, including an elevated risk of admission at the ICU, length of stay at the ICU, need for mechanical ventilation and mortality [ 75 , 273 , 274 ]. Vitamin D presents well-known extra-skeletal properties, including the regulation of both innate and adaptive immunity as well as enhanced activity against viruses, bacteria and fungi through the induction of cathelicidin and defensins [ 275 , 276 , 277 ]. Moreover, the beneficial effects of vitamin D have been consistently acknowledged in cardiometabolic, respiratory, neurocognitive and musculoskeletal health [ 278 , 279 , 280 , 281 , 282 , 283 ].…”
Section: Laboratory Findings and Biomarkers In Long Covidmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence based on meta-analyses, observational prospective and retrospective studies, and interventional studies has shown associations between hypovitaminosis D and the occurrence of acute severe COVID-19, including an elevated risk of admission at the ICU, length of stay at the ICU, need for mechanical ventilation and mortality [ 75 , 273 , 274 ]. Vitamin D presents well-known extra-skeletal properties, including the regulation of both innate and adaptive immunity as well as enhanced activity against viruses, bacteria and fungi through the induction of cathelicidin and defensins [ 275 , 276 , 277 ]. Moreover, the beneficial effects of vitamin D have been consistently acknowledged in cardiometabolic, respiratory, neurocognitive and musculoskeletal health [ 278 , 279 , 280 , 281 , 282 , 283 ].…”
Section: Laboratory Findings and Biomarkers In Long Covidmentioning
confidence: 99%
“…Interestingly, microbiota transfer from individuals with LC provoked a decline in brain cognitive properties and dysfunctional lung defense in mice, which was partially prevented by the administration of the commensal probiotic Bifidobacterium longum [ 292 ]. Probiotics, prebiotics and synbiotics, which have shown beneficial metabolic and immunologic properties [ 277 , 288 , 293 , 294 ], could be used as adjunct therapeutic tools in LC in the future. Finally, although there are no data on mycobiota alterations in LC, a study has found increased levels of fungal translocation from the gut and/or the lung epithelia, determined by β-glucan, a fungal cell wall polysaccharide, in the plasma of individuals of LC, suggesting the important role of fungal translocation in chronic immune activation due to gut barrier permeability [ 295 ].…”
Section: Laboratory Findings and Biomarkers In Long Covidmentioning
confidence: 99%
“…Several studies have demonstrated a shift towards healthier behavior after cancer diagnosis or treatment [178][179][180][181][182][183]. Whereas the majority of evidence on lifestyle changes after cancer diagnosis or treatment has been drawn from female breast cancer survivor cohorts [180,183,184], several studies have focused on hematologic malignancies [180,[185][186][187][188].…”
Section: Lifestyle Changes (Diet and Exercise) And Cancer Survivorshi...mentioning
confidence: 99%
“…The lack of medications for COVID-19 in the early phases of the pandemic led the public to seek alternative therapies, including nutraceuticals. Bader-Larsen et al evaluated the safety of “anti-COVID-19” nutraceuticals in patients with cancer [ 61 ]. They reported that the use of vitamin C, vitamin D and selenium supplements is likely safe at typically recommended doses.…”
mentioning
confidence: 99%